The Role of Work Attitude in Mediating the Influence of Corporate Culture and Management Support on the Work Productivity of PLN Employees - Selviani, Ni Wayan Putri; Rahmawati, Putu Indah; Heryanda, Komang Krisna (International Journal of Science and Society, 2024)
This research investigates the role of work attitude as a mediator in the relationship between corporate culture, management support, and employee work productivity. Corporate culture and management support are key factors influencing employee productivity. However, there has been no research that thoroughly explores how work attitude mediates the influence of both on work productivity. The population that researchers use is employees of PT PLN (Persero) East Bali Customer Service Implementation Unit (UP3). With as many as 119 employees, the sample was determined with the census method; therefore, the whole population made the sample study. Next, data was collected through distributing questionnaires via Google Forms. The existing data collected was furthermore analyzed with SEM-PLS. The study results find That corporate culture positively affects employee work productivity. Management support has a positive role in the work productivity of PT PLN East Bali employees. Work attitude has a positive role in the work productivity of PT PLN East Bali employees. Corporate culture has a positive effect on the work attitude of PT PLN East Bali employees. Management supports a positive role in the work attitude of PT PLN East Bali employees. Work attitude can mediate the influence of corporate culture on the work productivity of PT PLN East Bali employees. Work attitude can mediate the influence of management support on the work productivity of PT PLN East Bali employees. Expected study: This Can be theoretical and practical in developing human resource management literature and guiding practitioners to increase the effectiveness of management strategies in a competitive work environment.